Les mots de la démocratie participative en ligne : le préformatage de la doxa à travers les outils de la civic tech - Ana-Maria Cozma; Olga Galatanu (Romania, 2022)
Words that Shape Online Participatory Democracy: the Implicit Representations of Civic Tech Tools. This paper focuses on the online consultations called ‘Estates General of Bioethics’ that took place in France in 2018. It examines the words that configure and structure the consultations’ website. Our aim is to show what impact ready-to-use platforms for democratic consultations have on people’s representation of democracy. We will first discuss the enunciative responsibility shared by the three entities involved in the organisation of the consultations: the government, the CCNE and the start-up firm Cap Collectif. Then, within the framework of the Semantics of Argumentative Possibilities, we will describe the implicit representation of democracy that emerges from the consultations’ website and compare it to the meaning potential of the word ‘democracy’. This will lead us to a series of conclusions, regarding the aspects of democracy that the website favours, the non-coincidence of the words used by the CCNE and by Cap Collectif, and the consequences of the semantic choices of online consultations.